(untitled) (Repertorio Científico, 2025)
Canopy gaps in mangroves are created because of the death of several standing trees that later fall, and they have circular o elliptical shape. Researchers in this topic suggest that the most likely cause is lightning strikes. The objective of this research was to characterize canopy gaps in the Tivives mangrove by determining their sizes, amount, location and conditions. Google Earth Pro images were used and field trips to some canopy gaps were carried out for characterization. Twenty-four canopy gaps were identified, with sizes between 2,403 and 74 m2, and average of 797 m2. These gaps were distributed all over the mangrove, but away from the canal edges. The characteristics of the canopy gaps in the Tivives mangrove were like those reported for other canopy gaps in mangroves of the world. However, the mangrove area affected by these gaps is among the largest reported.